Association between exposure to air pollutants and cardiovascular disease mortality in coastal area of eastern China - Cao, Yiwen; Zhou, Xiaoyun; Tang, Zaixiang (Frontiers in Public Health, 2025)
BackgroundThe impact of air pollutants on cardiovascular disease (CVD) mortality remains inadequately studied in Rudong, an eastern coastal area of China. This study aimed to investigate the association between air pollutants and CVD mortality in Rudong.MethodsDaily number of deaths from CVD, meteorological and air pollutants data in Rudong from 2013 to 2022 were collected. The generalized additive model (GAM) was employed to analyze the relationship between air pollutants and CVD mortality, and stratified analyses were conducted by gender, age, and season.ResultsThere was a significant association between air pollutants and CVD mortality. A total of 36,972 deaths from CVD-related deaths were included in the study. We observed that short-term exposure to PM2.5, PM10, SO2, CO, and O3 was positively correlated with CVD mortality. Per 10 μg/m3 increment in PM2.5 (lag05), PM10 (lag05), SO2 (lag05), CO (lag04), and O3 (lag06) (per 1 mg/m3 increment in CO), the excess risk of CVD mortality were 1.00% (95%CI:0.37%, 1.64%), 1.05% (95%CI:0.15%, 1.96%), 7.65% (95%CI:4.47%,10.94%), 13.82% (95%CI:4.47%,23.99%), and 1.82% (95%CI:1.02%, 2.62%), respectively. Overall, the estimated impact of air pollutants was greater in the warm season. In addition, susceptibility to air pollution exposure varied across different genders and age groups, with females and those over 65 years old being more sensitive.ConclusionExposure to air pollutants increased the risk of CVD mortality. Furthermore, the health effects of air pollution may be influenced by season, gender, and age. In conclusion, reducing pollutant concentrations to lower levels may provide greater cardiovascular benefits.